2018
DOI: 10.1080/25742981.2018.1552499
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the teaching personal and social responsibility model within preschool education: strengths, challenges and strategies

Abstract: The teaching personal and social responsibility (TPSR) model has been considered a valuable tool for children to reach their full potential in life. However, little research has been conducted with the TPSR model in preschool contexts. The purpose of the present study was to understand the experiences of a program leader while implementing a TPSR-based program within a preschool setting. The participants were 24 children with 5 years of age attending a school located in the north of Portugal, and the program l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 39 publications
0
25
0
2
Order By: Relevance
“…Salah satu fokus dari permainan olahraga tradisional 'Gobak Sodor' yang akan diterapkan adalah mampu menjadikan anak-anak memiliki tanggung jawab pribadi dan sosial dalam lingkungannya (Pavão, Santos, Wright, & Gonçalves, 2018). Tanggung jawab pribadi dan sosial dapat dilihat pada saat permainan berlangsung, bagaimana anak bertanggung jawab secara pribadi dengan tugasnya dalam permainan dan bertanggung jawab secara sosial dengan kelompoknya untuk mempertahankan garis batas yang sudah menjadi kewajiban untuk dijaga.…”
Section: Tanggung Jawab Pribadi Dan Sosialunclassified
“…Salah satu fokus dari permainan olahraga tradisional 'Gobak Sodor' yang akan diterapkan adalah mampu menjadikan anak-anak memiliki tanggung jawab pribadi dan sosial dalam lingkungannya (Pavão, Santos, Wright, & Gonçalves, 2018). Tanggung jawab pribadi dan sosial dapat dilihat pada saat permainan berlangsung, bagaimana anak bertanggung jawab secara pribadi dengan tugasnya dalam permainan dan bertanggung jawab secara sosial dengan kelompoknya untuk mempertahankan garis batas yang sudah menjadi kewajiban untuk dijaga.…”
Section: Tanggung Jawab Pribadi Dan Sosialunclassified
“…There have been more systematic and numerous examples of teaching social responsibility experiences by promoting responsibility in physical-sports activity (Belando et al, 2012;Richards et al, 2019) in various educational stages (Pavão et al, 2019). These programs have had very positive results (Ruiz et al, 2006;Caballero et al, 2013;Gordon and Doyle, 2015;Sánchez-Alcaraz et al, 2016;Andrew et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This broadening of TPSR from its origins in the USA has occurred over many years and has included many 'firsts'. Examples include the first study published on the use of TPSR in pre-school education in Portugal (Pavão, Santos, Wright, & Gonçalves, 2019), its introduction into higher education programs in Canada (Kell & Forsberg, 2014), Wright, White & Gaebler-Spira (2004) study with an adapted physical activity program, the first study linking TPSR fidelity and student outcomes (Pascual et al, 2011), and the translation of TPSR into Spanish and its subsequent introduction into physical education classes and school-wide applications in Spain (Escartí, Llopis-Goig, & Wright, 2017). There are many other 'firsts' that have occurred and this process of expanding the boundaries will continue as the popularity of TPSR increases, both within the USA and internationally, and as practitioners and academics continue to experiment with the model.…”
Section: Other Contexts and Populationsmentioning
confidence: 99%
“…While there were a relatively small number of in-school-based TPSR based programs reported in the USA (Hemphill, Templin, & Wright, 2013;Wright & Burton, 2008) this was a more popular context internationally. Two studies, one from Portugal (Pavão, et al, 2019) and one from New Zealand (Severinsen, 2014), reported on TPSR based programs that successfully worked with pre-school children. There have also been a number of programs that have worked with students at the elementary school level in a variety of countries.…”
Section: Other Contexts and Populationsmentioning
confidence: 99%